Effect of differential nitrogen doses on yield, fruit quality and foliar nutrient concentration of water apple (Syzygium javanica) - GHOSH, S N; BERA, B (The Indian Journal of Agricultural Sciences, 2014)
An investigation was made to know the effect of different levels of nitrogen on yield, fruit quality and foliar N, P and K status of water apple (Syzygium javanica) grown in laterite soil. The attempt was also made to find out the best time for leaf sampling for N, P and K estimation in water apple. There were four treatments, nitrogen at 0, 100, 200 and 300 g/tree/year which were applied at two splits, i e March and September following randomized design having six replications. Three consecutive years of investigation indicated that application of nitrogen at 200 g/tree along with 100 g P2O5, 100 g K2O and 20 kg FYM resulted in highest fruit production which was associated with the foliar N values of 1.40 to 1.44 %. The best time of leaf collection in water apple for N was the month of September–October (6-7 month old leaves) while for P and K it was July–August (4-5 month old leaves).